Contribution of forests and trees to food security and nutrition - Gitz, V.; Pingault, N.; Meybeck, A.; Ickowitz, A.; McMullin, S.; Sunderland, T.C.H.; Vinceti, B.; Powell, B.; Termote, C.; Jamnadass, Ramni H.; Dawson, Ian K.; Stadlmayr, B. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Because the expansion of agriculture (crop and livestock), and therefore food production, has been both historically and presently realized at the expense of forests, food security and forests are often perceived as antagonistic, and their relation characterized by inherent trade-offs. The reality, however, is much more complex, with forests and trees playing a key, yet largely unrecognized, role in sustaining food production and contributing to food security and nutrition (FSN) in its different dimensions. Conversely, because they impact on forests and trees, the considerable landscape changes driven by agricultural expansion also bring negative effects on the ecosystem services that sustain agricultural production itself, with potential impacts on the FSN status of local populations as well as on global food availability and food security (Sunderland et al. 2019).